Migration on wings : aerodynamics and energetics - Kantha, Lakshmi (SpringerBriefs in Applied Sciences and Technology,)
This book is an effort to explore the technical aspects associated with bird flight and migration on wings. After a short introduction on the birds migration, the book reviews the aerodynamics and Energetics of Flight and presents the calculation of the Migration Range. In addition, the authors explains aerodynamics of the formation flight and finally introduces great flight diagrams.